PENGARUH AKTIVA TETAP DAN MODAL TERHADAP LABA BERSIH PADA BANK PEMBANGUNAN DAERAH YANG LISTING DI BURSA EFEK INDONESIA - Olivia Olivia; Geby Geby; Anjelia Anjelia; Haryono Haryono (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2023)
This study analyzes the impact of fixed assets and capital on net gain from Regional Development Bank listed on the IDX from 2015 to 2019. This study uses an associative method, namely with the intention of finding out what causes the relationship between variables. The approach used is quantitative which consists of numbers to be measured by statistics that act as a data analysis tool. This research data is data or information obtained by researchers indirectly or commonly referred to as secondary data. This study looked at the Regional Development Banks listed on the IDX, including the Regional Development Bank of East Java Tbk (BJTM), Regional Development Banks of West Java (BJBR) and Banten Regional Development Bank Tbk (BEKS). This study used a data analysis technique called Multiple Linear Regression Analysis, which is a test used to check if a data set is Normally Distributed. In addition, testing the hypothesis so that the effect of variable independent on variable dependent partially or simultaneously can be known its significance. The data were analyzed using the IBM SPSS Statistics program.